Global Fund financing and human resources for health investments in the Eastern Mediterranean Region - Adeyemi Okunogbe; Diana Bowser; Gulin Gedik; Saha Naseri; Ayat Abu-Agla; Najibullah Safi (BMC, 2020)
Abstract Background Despite the large investments in donor-related health activities in areas of the globe prone to tension and conflict, few studies have examined in detail the role of these donor investments in human resources for health (HRH). Methods We used a mixed-methods research methodology comprising both quantitative and qualitative analyses to analyze the Enhanced Financial Reporting System of the Global Fund to Fight AIDS, Tuberculosis and Malaria budget and expenditure data from 2003 to 2017 for 13 countries in the Eastern Mediterranean Region (EMR). We analyzed additional detailed budgetary data over the period 2015-2017 for a sub-set of these countries. Two country-case studies were conducted in Afghanistan and Sudan for a more in-depth understanding of the HRH-related activities that occurred as a result of Global Fund grants. Results The results show that US$2.2 billion Global Fund dollars had been budgeted and US$1.6 billion were expended over the period 2003-2017 in 13 Eastern Mediterranean countries. The average expenditures for human resources for health (training and human resources) as a percentage of total expenditure are 28%. Additional detailed budgetary data analysis shows a more conservative investment in HRH with 13% of total budgets allocated to "direct" HRH activities such as salaries, training costs, and technical assistance. HRH-related activities supported by the Global Fund in Afghanistan and Sudan were similar, including pre-service and in-services training, hiring of program coordinators and staff, and top-ups for clinical staff. Conclusions HRH remains a key issue in strengthening the health systems of low- and middle-income countries. While this study suggests that Global Fund's HRH investments in the EMR are not lagging behind the global average, there appears to be a need to further scale up these investments considering this region's unique HRH challenges.